Studying the Effect of Some Organic Sulfur Compounds as Flame Retardants for Polyester and Epoxy Resins - Hanan Qais Al-Masoudi (Journal of Global Pharma Technology, 2018)
In this work, five additives were used, namely; Pentane -2,3,4-trione3-[(5,6-diphenyl-6H-1,3,4-thiadiazin-2-yl)hydrazine]) (Additive I).(5-[(z)-(5,6-diphenyl-6H-1,3,4-thiadiazin-2-yl)diazenyl]-4,6dimethyl-2H-1,3-thiazin-2-amine)(AdditiveII).( (4Z,6E)-6-((Z)-(5,6-diphenyl-6H-1,3,4thiadiazin-2-yl)diazenyl)-5,7-dimethyl-2,3-dihydro-1,4-thiazepine-3 carboxylic acid)(Additive III).(6-[(5,6-diphenyl-6H-1,3,4-thiadiazin-2yl)diazenyl]-5,7dimethyl-1,3,4-thiadiazepin-2-amine) (Additive IV). (2,2- (1,4-phenylene)bis (4,5-dihydro1,thiazole-4-carboxylicacid) (Additive V).The effects of these additives on flammability of unsaturated polyester and epoxy resins have been studied. Sheets of the resins with weight percentages of (0.2, 0.4, 0.6 & 0.8 %) of the additives in dimensions (150×150×3) mm were used. Two standard test methods used to measure the flame retardation are: (ASTM: D-2863) and (ASTM: D-635).Results are obtained from these tests indicated that, additive IV has high efficiency as flame retardant, self–extinguishing (S.E.) at the percentage (0.2 %) for unsaturated polyester resin and the percentage (0.4 %) for epoxy resin. Also self- extinguishing (S.E.) at the percentage (0.4%) for additives II in unsaturated polyester resin and the (0.6%) for additives II in epoxy resin Additive V show low effect on flammability in both resinsKeywords: Sulfur compounds; Organic sulfur compounds; Additives; Flame retardants; Flammability; Unsaturated polyester resin; Epoxy resin; Thermosetting polymer.